Category management for the operational resource procurement - Ivan Elyashevich; Victor Sergeev; Valentina Dybskaya; Anastasia Ivanova (Journal of Innovation & Knowledge (JIK), 2024)
The introduction of Category Management in operational resources purchasing helps to improve logistics service levels and increase the profitability of industrial enterprises. There are two main purposes of the provided article. The first purpose is to develop a methodological framework for category management of operational resources supply for large industrial enterprises. Secondly, it aims to offer a mechanism for inter-organizational collaboration with suppliers and contractors in supply chains. This study is based on the methods of forecasting of the uncertain stock demand. Time-series and correlation-regression models are used for forecasting. The first finding of the research is the systematization and classification of the operational resources purchased by industrial enterprises. Modified models of operational resources inventory management and a methodology for assessing tied-up losses are offered in this article and, they are based on category management. A developed methodology allows one to make strategic decisions in the field of procurement. According to the preliminary estimates, implementation of the proposed approaches increases net profit in large industrial companies by 4-5 % in relative periods.
Keywords: L11; L05; L06; 650; Inventory requirement planning; Logistics service level; Maintenance; Optimization of purchasing process; Repair and operations